2016
DOI: 10.1136/tobaccocontrol-2016-053116
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette use is differentially related to smoking onset among lower risk adolescents

Abstract: Objective E-cigarette use has been linked to onset of cigarette smoking among adolescents but some commentators have suggested that this simply reflects high-risk adolescents being more likely to use e-cigarettes and to smoke. We tested whether the effect of e-cigarette use for smoking onset differs for youth who are lower vs. higher on propensity to smoke. Methods School-based survey with a longitudinal sample of 1,136 students (9th – 11th graders, mean age 14.7 years) in Hawaii, initially surveyed in 2013 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 44 publications
3
91
0
Order By: Relevance
“…This analysis concluded, consistent with earlier smaller longitudinal studies, 5,6 that e-cigarette-only users had risk profiles that made them unlikely to initiate tobacco product use with cigarettes.…”
supporting
confidence: 85%
“…This analysis concluded, consistent with earlier smaller longitudinal studies, 5,6 that e-cigarette-only users had risk profiles that made them unlikely to initiate tobacco product use with cigarettes.…”
supporting
confidence: 85%
“…1418 Never-smoking low-risk youth who use e-cigarettes may be more likely to go on to initiate cigarette smoking compared with never-smoking low-risk youth who are not using e-cigarettes. 39 Two cross-sectional studies in youth 40, 41 indicate that, like adults, 42 youth smokers who are using e-cigarettes want to quit but are less likely to be former smokers. Many e-cigarette users also smoke cigarettes, 43 but this fact does not change the finding that e-cigarettes appear to be attracting some low-risk youth.…”
Section: Discussionmentioning
confidence: 99%
“…7 -10 Moreover, recent research with different designs has shown that e-cigarettes are most strongly related to smoking onset among lower-risk adolescents, thus specifically contradicting the confounding hypothesis. 9,12 Data from Demissie et al 3 do raise the possibility of an underlying vulnerability (not previously measured) that produces both e-cigarette use and smoking. As the authors discuss, the risk behaviors they assessed could derive from rejection of conventional social norms 13 or from activation of common neural pathways by nicotine, 14 and such hypotheses need to be tested.…”
Section: But Weren't They Going To Smoke Anyway?mentioning
confidence: 98%